Extrahepatic undifferentiated embryonal sarcoma, cytology as an accurate method for early diagnosis: an extremely rare case report in an Indian child - Rastogi, Nupur; Tanwar, R. K.; Saxena, B. (International Journal of Research in Medical Sciences, 2019)
Undifferentiated embryonal sarcoma has been described in the liver, a rare malignant mesenchymal neoplasm, that occurs primarily in children and teenagers. Approximately 260 cases have been reported arising in the liver since 1978 when this disease was first described. Its pathogenesis is still obscure. Authors presented a case of extrahepatic undifferentiated embryonal sarcoma in a 9-year-old female presenting with upper abdominal dull pain. Ultrasound and CT Scan showed normal liver architecture, with liver pushed upwards due to compression by tumor arising in the retroperitoneum. To the best of our knowledge, this is first case of extrahepatic undifferentiated embryonal sarcoma diagnosed on cytomorphology and confirmed by histopathology and immunohistochemistry markers.